Standardization of Epidemiological Surveillance of Acute Rheumatic Fever . (15th September 2022) - Scheel, Amy; Beaton, Andrea Z; Katzenellenbogen, Judith; Parks, Tom; Miller, Kate M; Cherian, Thomas; Van Beneden, Chris A; Cannon, Jeffrey W; Moore, Hannah C; Bowen, Asha C; Carapetis, Jonathan R
Abstract: Acute rheumatic fever (ARF) is a multiorgan inflammatory disorder that results from the body's autoimmune response to pharyngitis or a skin infection caused by Streptococcus pyogenes (Strep A). Acute rheumatic fever mainly affects those in low- and middle-income nations, as well as in indigenous populations in wealthy nations, where initial Strep A infections may go undetected. A single episode of ARF puts a person at increased risk of developing long-term cardiac damage known as rheumatic heart disease. We present case definitions for both definite and possible ARF, including initial and recurrent episodes, according to the 2015 Jones Criteria, and we discuss current tests available to aid in the diagnosis. We outline the considerations specific to ARF surveillance methodology, including discussion on where and how to conduct active or passive surveillance (eg, early childhood centers/schools, households, primary healthcare, administrative database review), participant eligibility, and the surveillance population. Additional considerations for ARF surveillance, including implications for secondary prophylaxis and follow-up, ARF registers, community engagement, and the impact of surveillance, are addressed. Finally, the core elements of case report forms for ARF, monitoring and audit requirements, quality control and assurance, and the ethics of conducting surveillance are discussed. Abstract : This article presents case definitions for acute rheumatic fever and best practice protocols for conducting epidemiological surveillance for acute rheumatic fever in a variety of settings.